The Correlation of Giardiasis with Nutritional Status in Primary School Age Children at SD INPRES 104222 and SDN 101828 in Sei Glugur Village, Pancur Batu District - Evita Sola Gracia; Adelina Haryani Sinambela (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background. Giardia lamblia is a protozoan that causes an intestinal infection called giardiasis. This infection can cause the process of absorption of nutrients is not optimal. Giardiasis can result in a decrease in nutritional status. The aim of study is to determain the relationship between giardiasis and nutritional status at the age of elementary school children. Method. This is cross-sectional study of 114 students at SD INPRES 104222 and 101828 in Sei Glugur Village in Pancur Batu District. Primary data collection was carried out by anthropometric examination and examination of stool samples using the formol ether concentration technique at the Parasitology Laboratory of the Faculty of Medicine, Universitas Sumatra Utara. Results. From 114 children who met the inclusion criteria, the incidence of Giardia lamblia infection was 7%. Based on the weightÂ for height index, 8 (7%) people had poor nutritional status, 61 (53.5%) people with underweight nutritional status 27 (23.7%) people with moderate nutrition and 12 (10,5%) people with good nutrition. Overweight by 1 (0.9%) person and obese 5 (4.4%) people. There is no correlation between giardiasis infection with weight for height (p>0.05). Conclusion. The incidence of Giardia lamblia infection was low and there was no correlation between giardiasis with nutritional status in primary school-age children.